Adaptation of Aesthetic Experiences as a Method For Creating The Bidhuh Dance - Nareswari, Wintang Murti; Maharani Luthvinda Dewi; Nandhang Wisnu Pamenang (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
This research aims to analyze the Tulungagung Reog Kendang Dance as the primary inspiration for the Bidhuh Dance. The central focus of this study is to explore the choreographer's process in utilizing the Tulungagung Reog Kendang Dance as a source of inspiration for the Bidhuh Dance, as well as to examine the formal characteristics of the Bidhuh Dance. A qualitative research methodology is employed, with findings presented in descriptive form. Data collection techniques consist of three stages: observation, interviews, and documentation. The findings indicate that the Bidhuh Dance is a creative work inspired by the Tulungagung Reog Kendang Dance, characterized by the deconstruction of fundamental movements and the incorporation of Dhodhog beat patterns through body percussion as an idiom.